Isotope Tracing Untargeted Metabolomics Reveals Macrophage Polarization-State-Specific Metabolic Coordination across Intracellular Compartments - Puchalska, Patrycja; Huang, Xiaojing; Martin, Shannon E.; Han, Xianlin; Patti, Gary J.; Crawford, Peter A. (iScience, 2018)
We apply stable isotope tracing, mass-spectrometry-based untargeted metabolomics, to reveal the biochemical space labeled by C-substrates in bone-marrow-derived macrophages. At the pathway level, classically (lipopolysaccharide [LPS]-polarized, M1) and alternatively (interleukin [IL]-4-polarized, M2) polarized macrophages were C-labeled with surprising concordance. Total pools of uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), an intermediate in the hexosamine biosynthetic pathway, were equally abundant in LPS- and IL-4-polarized macrophages. Informatic scrutiny of C-isotopologues revealed that LPS-polarized macrophages leverage the pentose phosphate pathway to generate UDP-GlcNAc, whereas IL-4-polarized macrophages rely on intact glucose and mitochondrial metabolism of glucose carbon. Labeling from [ C]glucose is competed by unlabeled fatty acids and acetoacetate, underscoring the broad roles for substrate metabolism beyond energy conversion. Finally, the LPS-polarized macrophage metabolite itaconate is imported into IL-4-polarized macrophages, in which it reprograms [ C]glucose metabolism. Thus, use of fully unsupervised isotope tracing metabolomics in macrophages reveals polarization-state-specific metabolic pathway connectivity, substrate competition, and metabolite allocation among cellular compartments.